Periodic mesoporous silicas and organosilicas: an overview towards catalysis - Shylesh, S.; Samuel, Prinson P.; Sisodiya, Sheetal; Singh, A. P. (Catalysis Surveys from Asia, 2008)
Micelle-templated mesoporous and organic-inorganic hybrid mesoporous materials are important in many fields of material research, especially for hosting catalysts in confined space. Among this class, the recent discovery of periodic mesoporous organosilicas (PMOs) represent an exciting new group of organic-inorganic nanocomposites targeted for a broad range of applications ranging from catalysis to microelectronics. Compared to the earlier generation of organic-inorganic hybrid mesoporous samples, obtained by the cocondensation reaction or by the grafting reaction, PMOs represent the right combination of organic and inorganic groups in the frame wall positions. This article reviews the current state of art in organic-inorganic hybrid mesoporous material research with special emphasis over periodic mesoporous organosilica materials having various redox centers (Ti, V, Cr) suitable for oxidation reactions as well as acidic sites (Al, -SO(3)H) for the organic transformation of bulky molecules.
Keywords: Acid catalysis; epoxidation; Mesoporous organosilicas; Organic-inorganic hybrid materials